Enhanced fatigue damage resistance of nanotwinned austenitic grains in a nanotwinned stainless steel. (15th July 2017) - Li, Q.; Yan, F.K.; Tao, N.R.
Abstract: The fatigue damage behavior of a novel nanotwinned stainless steel consisting of nanotwinned austenitic grains, nanograins and dislocation structures was investigated. It is found that the nanotwinned grains can effectively suppress the generation of persistent-slip-bands-like shear bands and nucleation of fatigue cracks in comparison with the other two deformed regions. Such better fatigue damage resistance of nanotwinned grains is mainly ascribed to the higher microstructural stability of them without obviously structural coarsening. Graphical abstract: